2017
DOI: 10.1140/epjc/s10052-017-4764-2
|View full text |Cite
|
Sign up to set email alerts
|

$$\gamma \gamma \rightarrow M^{+}M^{-}(M=\pi , K)$$ γ γ → M + M - ( M = π , K ) processes with twist-3 corrections in QCD

Abstract: We study the γ γ → M + M − (M = π, K ) processes with the contributions from the two-particle twist-2 and twist-3 distribution amplitudes of pion and kaon mesons on BHL prescription in the standard hard-scattering approach. The results show that the contributions from twist-3 parts are actually not power suppressed compared with the leading-twist contributions in the low energy region. The cross sections with twist-3 corrections agree well with the experimental data in the two-photon center-of-mass energy W > … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(171 citation statements)
references
References 49 publications
6
164
1
Order By: Relevance
“…However, these materials needed to improve their thermal insulation characteristics in order to be comparable with the commercial phenol-formaldehyde based aerogels. 121 From the above discussion, it can be concluded that lignin can be successfully substituted with phenol (either partially or completely) in phenol formaldehyde resins. However, the lignin extracted from pine sawdust by an organosolv-extraction allowed the substitution of phenol to produce viscous resol-type phenolic resins.…”
Section: Grishechko Et Al Havementioning
confidence: 92%
“…However, these materials needed to improve their thermal insulation characteristics in order to be comparable with the commercial phenol-formaldehyde based aerogels. 121 From the above discussion, it can be concluded that lignin can be successfully substituted with phenol (either partially or completely) in phenol formaldehyde resins. However, the lignin extracted from pine sawdust by an organosolv-extraction allowed the substitution of phenol to produce viscous resol-type phenolic resins.…”
Section: Grishechko Et Al Havementioning
confidence: 92%
“…and Hiyama [15][16][17] reactions, in the Larock heteroannulation reaction, [18][19][20][21] for the degradation of pollutants, 22 for hydrogenation 23 and in fuel cells. 24 In recent years, it has been proven that the use of complex functional groups, either graed or smeared onto solid supports, plays an important role in preventing the aggregation of metal catalysts.…”
Section: -14mentioning
confidence: 99%
“…The torque is determined by α D,l − α D,s , the external concentration gradient ∇c, and the blade orientation θ. Considering eqn (6) the steady angular velocity reads (7) Note that the proposed diffusiophoretic micro-turbine is significantly different from existing catalytic self-propelled rotors [29][30][31][32][33][34][35][36] in driving mechanisms and potential applications. The rotation is generated from the diffusive mass flux in a constant concentration gradient, which resembles very much what a conventional turbine does in a convective flow, such as a water turbine.…”
Section: Theory: Anisotropic Diffusiophoresis and Diffusiophoretic MImentioning
confidence: 99%